Becoming Paul, becoming Christ: the Nag Hammadi "Apocalypse of Paul" (NHC v,2) in its Valentinian context - Twigg, M (2015)
This thesis seeks to demonstrate the Apocalypse of Paul’s position within the broader Valentinian literary corpus from the Nag Hammadi codices. Previous scholars, notably William Murdock and Michael Kaler, have gestured in this direction, but no attempt has been made to systematically situate the Apocalypse of Paul in relation to other Valentinian sources. Quite possibly this desideratum exists because although the Apocalypse of Paul’s debt to Jewish apocalypticism is self-evident, scholars of Valentinianism have generally neglected those ideas in Valentinian literature which are derived ultimately from Judaism, often received via Paul or other New Testament writers. These would include the notion of the Name of God as a saving power, even a soteriological agent, and the image of a surrogate heavenly temple through which favoured adepts may ascend in the present. These come to be combined in Valentinian thought through a high-priestly Christology in which it is by virtue of bearing the Divine Name that one may enter this ideal temple in the fashion of the old Jewish high priest, and now Christ. On the other hand, Valentinians downgrade the biblical creator-God to the level of an imperfect demiurge, placing him in an inferior heavenly temple while supplanting the Pleroma atop him as the true spiritual temple housing the Father of Christ. The development of this constellation of ideas is traced principally from Valentinus himself, through the Gospel of Truth and the Excerpts from Theodotus, to the Gospel of Philip, where it receives its most extensive explication. It is argued that the Apocalypse of Paul consciously builds on this intellectual current using the apostle’s image in order to construct an ideal authoritative account of how such ascent ought to appear among Valentinian initiates and thereby contribute to the rhetorical and psychological construction of future experiences among the elect community.